2018
DOI: 10.4314/tjpr.v16i12.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic consumption of energy drinks on liver and kidney of experimental rats

Abstract: Purpose: To investigate the effects of chronic intake of a brand of energy drink (ED) on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
6
16
1
Order By: Relevance
“…Another possible explanation for the alteration in these parameters is the ureainduced activation of xanthine oxidase, which accelerates the rate of uric acid biosynthesis from xanthine (Obochi et al, 2010). In contrast to previous studies that reported a significant increase in serum creatinine levels, no significant changes were detected in the current study which can be explained by the shorter experimentation period in this study compared to the previous reports (Mansy et al, 2017). Peroxide free radicals are excessively produced as a result of the oxidative stress induced by the persistent hyperglycemia, eliciting renal oxidative damage in the form of interstitial inflammation, increased proteinuria and histopathological changes of the renal tissue (Gheith, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for the alteration in these parameters is the ureainduced activation of xanthine oxidase, which accelerates the rate of uric acid biosynthesis from xanthine (Obochi et al, 2010). In contrast to previous studies that reported a significant increase in serum creatinine levels, no significant changes were detected in the current study which can be explained by the shorter experimentation period in this study compared to the previous reports (Mansy et al, 2017). Peroxide free radicals are excessively produced as a result of the oxidative stress induced by the persistent hyperglycemia, eliciting renal oxidative damage in the form of interstitial inflammation, increased proteinuria and histopathological changes of the renal tissue (Gheith, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…It is to be noted that both heart and liver tissues did not show pathological changes despite the biochemical changes observed in the animals' lipid profile. This can possibly be assigned to the relatively short duration of the current experiment in comparison to the other studies that showed changes in the liver tissue after 12 weeks of ED administration (Mansy et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…These results were in agreement with Reis et al [27] and Mansy et al [28] . Seifert et al [2] found that these effects may be caused by the mixture of various ingredients in the ED due to synergistic interaction and augmented oxidative effect of them.…”
Section: Discussionsupporting
confidence: 93%
“…Also, Attia and Nasr [38] found that the suppression of AChE resulted in the cumulation of acetylcholine (ACh), that may cause lymphocytes stimulation and elevated cellular cyclic guanosine monophosphate concentration, increased lymphocyte motility and cytotoxicity. Mansy et al [28] explained the congestion of blood vessels by microcirculatory disturbance that caused by energy drink intake. Also, Kassab and Tawfik, [41] mentioned that ED had been associated with many cardiovascular disorders as well as increased platelet aggregation and impaired endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in RB treated group there were a decrease in SOD and GSH levels in the pancreatic tissue. This result was in accordance with that of Mansy et al [19] who gave two oral doses of energy drink (1.1 and 2.2 ml/100g body weight/day) for 12 weeks and reported a significant decrease in SOD. Also, Al-Eryani et al [20] reported a significant decrease in GSH in homogenized testes after administration of Red Bull and Power Horse for 7 weeks.…”
Section: Energy Drinksupporting
confidence: 92%